Magnetic resonance-only rapid on-table planning and immediate treatment for spine metastases - Jerrold E. Kielbasa; Logan Kimble; Justin Rineer; Cameron W. Swanick; Patrick Kelly; Amish P. Shah (Physics and Imaging in Radiation Oncology, 2025)
Background and purpose: This work aims to develop a magnetic resonance (MR)-only treatment planning protocol for integration into magnetic resonance simulation (MR-SIM), on-table treatment planning, and immediate treatment workflow for rapid palliation of painful spine metastases. Materials and methods: Thirty-five treatment plans from healthy volunteers were generated on MR-SIM scans using a protocol including: (1) a library of 4 planning target volume (PTV) structures based on vertebral level, (2) default beam templates covering the PTVs while avoiding organs at risk (OAR), (3) bulk density assignments for dose calculations, and (4) a single set of dose optimization parameters. We transferred each plan to the patient’s prior computed tomography simulation (CT-SIM) images and compared dosimetric parameters. A time study was performed on the MR-SIM, on-table planning, and immediate treatment workflow for all 35 cases using healthy volunteers. Results: All bulk density MR-SIM plans resulted in acceptable dose distributions, with 100 % deemed appropriate for treatment by two physicians. The maximum point dose was within 3.2 %, and the minimum dose to 90 % of the target volume was within 2.8 % of the prescription dose. The time study demonstrated that the proposed workflow could be completed in a mean time of 23.6 min for the 3 Gy (10 fractions) plan and 25.4 min for the 8 Gy (single fraction) plan, from patient placement to treatment completion. Conclusion: These results demonstrate that safe, fast palliation of spine metastases can be achieved in under 30 min using MR-SIM, bulk density on-table planning, and immediate treatment delivery.